Set of Simulators of the Electrophysiology of the A-Type Potassium Current (IA) in Neurons - Pérez Bonilla, María Eugenia; Reyes Monreal, Marleni; Pérez Escalera, Miguel Felipe; Reyes Lazalde, Arturo (Revista Mexicana de Ingenieria Biomedica, 2020)
The A-type potassium current (IA) participates in important brain functions, including neuronal excitability, synaptic integration, and regulation of action potential patterns and fring frequency. Based on the characterization of its electrophysiological properties by current and voltage clamp techniques, mathematical models have been developed that reproduce IA function. For such models, it is necessary to numerically solve equations and utilize hardware with special speed and performance characteristics. Since specifc software for studying IA is not found on the Internet, the aim of this work was to develop a set of simulators grouped into three computer programs: (1) IA Current, (2) IA Constant-V Curves and (3) IA AP Train. These simulators provide a virtual reproduction of experiments on neurons with the possibility of setting the current and voltage, which allows for the study of the electrophysiological and biophysical characteristics of IA and its eﬀect on the train of action potentials. The mathematical models employed were derived from the work of Connor et al., giving rise to Hodgkin-Huxley type models. The programs were developed in Visual Basic® and the diﬀerential equation systems were simultaneously solved numerically. The resulting system represents a breakthrough in the ability to replicate IA activity in neurons.